Collaboration Between Islamic Religious Education Teachers And Counseling Guidance Teachers In Overcoming Student Delinquency At Smpn 9 Bima City - Siti Tazkirah; Klis Dianti; Muhammad Firdaus; Misnawati; Ruslan (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to examine the response to collaboration between PAI and BK teachers at SMPN 9 Bima City related to the issue of student delinquency. The focus of the research is on how the collaboration between the two groups of teachers in dealing with student delinquency. The research method used is field research with a qualitative approach, with data collection techniques including observation, interviews, and documentation. The results showed that PAI teachers focused more on the religious and moral aspects of students, while counseling teachers paid more attention to the psychological aspects and provided diagnosis and treatment of student delinquency. The cooperation between the two groups of teachers is coordinative, competitive, productive, evaluative, and transparent. The program receives strong support from the principal and other teachers who are concerned about changes in student behavior. The main obstacles come from the lack of cooperation from some homerooms and students’ resistance and closedness to the guidance and solutions offered.